Challenge of the game - athletes' skills: The role of flow theory orthogonal model in ultra marathon athletes - Stavrou, N. A.; Bagios, I.; Noutsos, K.; Psychountaki, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The concept of flow has been described as an optimal subjective mental state. A central issue of flow theory is that whether or not an athlete is in flow depends on his/her perception of the existing challenges and the nature of his/her skills (Csikszentmihalyi, 1982). When the challenges and skills are perceived as being in balance, in a high level, the athlete experiences flow. When the skills outperform the challenge, there is relaxation, whereas when the skills and challenges are below average, there is apathy, and, finally, when the challenges outweigh the skills, there will be anxiety (Csikszentmiahlyi, 1982). The purpose of the study was to examined the role of subjective estimation of challenge of the competition and athlete`s skills in the quality of their experience. Methods: One hundred and fifteen athletes participate in the present study, ranging in age from 26 to 66 years (Ì = 40.31, SD = 7.98). Just after the competition, the athletes completed the Flow State Scale - Short Form (FSS-SF; Jackson, Martin, & Eklund, 2008), and five 11point Likert type scales measuring (a) challenge of the game, (b) athlete`s skills, (c) stress, (d) activation and (e) subjective estimation of performance. The race length was 44 km, the higher altitude 2800m and the mean duration of the competition was approximately 7 hours. Results: The results indicated significantly higher correlations between athletes` skills and FSS-SF subscales compared to the value of the correlations of perceived challenge of the game. The athletes in the flow and relaxation quadrants revealed higher values of flow experience compared to the athletes of the other two states, sustaining significant differences among the four states (Wilks` d = .629, F3,100 = 1.719, p<.05, n2p =.143). Significant correlations revealed among activation and flow experience. Finally, no significant differences revealed in athletes' performance among the four states. Discussion: Athletes` quality of experience is differentiated among the quadrants of the orthogonal model. Specifically, the results suggest that the perception of skillfulness is essential for the athlete to experience positive mental states, compared to the perception of challenge. The importance of athletes` skills on the quality of their experience is further supported by the significantly higher correlations between the FSS-SF factors and the perceived skills, suggesting a close relationship, compared to the correlations between the FSS factors and perceived challenges. Finally, activation appears as an important factor for flow experience.